Revision of the Afrotropical genus Tritonus Mulsant (Coleoptera: Hydrophilidae) - Short, Andrew Edward Z. (Zootaxa, 2008)
The previously monotypic genus Tritonus Mulsant is revised. Six new species are described from Madagascar, from which the genus is also recorded for the first time: T. complanatus sp.n., T. crenulatus sp.n., T. madagascarensis sp.n., T. riambavy sp.n., T. riana, sp.n., and T. steineri sp.n. New records for the previously described and Mauritian-endemic species Tritonus cribratus (Mulsant) are given. All known species occur in hygropetric habitats, consistent with the biology of other members of the Oocyclus-genus group of the tribe Laccobiini to which Tritonus belongs. A key to species, aedeagal illustrations, and scanning electron micrographs of diagnostic characters are provided.